The Effect of Portfolio Diversification, Systematic Risk, and Stock Liquidity on Individual Investor's Portfolio Performance - Fauziyah Fadhilah; Vivi Natasha; Fariza Putri Hawa; Hasna Khalisha Putri; Mahesa; Maria Yovita R Pandin (International Publisher, 2025)
This study aims to analyze the influence of portfolio diversification, systematic risk, and stock liquidity on the portfolio performance of individual investors. The research approach used is quantitative with primary data obtained through the distribution of questionnaires to individual investors active in the Indonesian capital market. Sampling was carried out using the purposive sampling method with the criteria of respondents who have at least six months of investment experience. The collected data was analyzed using SPSS through validity, reliability, classical assumption tests, and multiple linear regression analysis. The results of the study show that simultaneously the variables of portfolio diversification, systematic risk, and stock liquidity have a significant effect on the portfolio performance of individual investors. Partially, systematic risk has a positive and significant effect on portfolio performance, while portfolio diversification and stock liquidity do not show a significant effect. These findings indicate that the characteristics of the Indonesian capital market, which are still sensitive to external factors, cause systematic risk to become the dominant factor in determining portfolio performance. This research is expected to contribute to individual investors in understanding the importance of market risk management and the implementation of effective diversification strategies.